Management of instruction for a CAI on social studies - Mana, Ofelia G. (Animo Repository, 1989)
The main purpose of computer-aided instruction (CAI) is to assist in the teaching and learning process. The quality of learning can be improved directly by tailoring the course to the needs of individual students. CAI has matured in the United States. Among the Asian countries, Hongkong and Singapore have embarked on programs to bring the computer to all High School classrooms. Unfortunately, CAI in the Philippines is still in its infancy stage. CAI softwares available in the country are, generally, American-oriented. Thus, this research aims to conceptualize the idea of creating a CAI software that is tailored to the needs of Filipino higher level elementary grade students. The CAI software specifications will be derived from comparative study and analysis done on several existing CAI softwares. Then a CAI will be written to help facilitate the teaching and learning process specifically for the course on Social Studies. In the application program, the computer performs a series of management functions on behalf of the teacher and the student. Thus, the research will help teachers in the process of integrating CAI into their teaching and help those involved in development work to improve the quality of the product.